Tomographic active optical trapping of arbitrarily shaped objects by exploiting 3D refractive index maps - Kyoohyun Kim (Nature Portfolio, 2017)
Controlling the three-dimensional behaviour of arbitrarily shaped and oriented particles with optical tweezers is a challenging task. Here, Kim and Park use tomographic active trapping to manipulate non-spherical particles and particle ensembles as well as biological cells.